Nonperforming financing sebagai penentu utama financial distress - Muhammadinah Muhammadinah (Universitas Kristen Maranatha, 2026)
Financial distress in Islamic banks has become an important issue in maintaining financial stability and resilience. This study aims to identify the determinants of financial distress in Indonesian Islamic banks using panel regression analysis. The Hausman test was employed to select the appropriate model, and the random effect (RE) model was found to be the most suitable. The results reveal that nonperforming financing (NPF) has a significant positive effect on financial distress, while financing to deposit ratio (FDR) and operating expenses to operating income (BOPO) show no significant influence. These findings highlight that financing quality is the dominant factor in explaining distress, reinforcing the RGEC and CAMELS frameworks that emphasize asset quality as a key indicator of bank health. The study concludes that controlling problematic financing is crucial for sustaining Islamic banking stability. Policy implications suggest that the Financial Services Authority (OJK) should strengthen supervision of NPF ratios through an effective early warning system, while Islamic banks need to enhance risk management, credit analysis, and governance practices. Academically, this study enriches the literature on Islamic banking distress in Indonesia and provides new perspectives for global comparative studies. Limitations include the relatively small sample size and short observation period, and future research is recommended to expand data coverage and incorporate additional variables such as profitability, governance, and macroeconomic factors.